Learning Bodies The Body in Youth and Childhood Studies - Coffey, Julia; Budgeon, Shelley; Cahill, Helen; SpringerLink (Online service) (Singapore : Springer Singapore (Imprint), 2016)
'Learning Bodies' addresses the lack of attention paid to the body in youth and childhood studies. Whilst a significant range of work on this area has explored gender, class, race and ethnicity, and sexualities - all of which have bodily dimensions - the body is generally studied indirectly, rather than being the central focus. This collection of papers brings together a scholarly range of international, interdisciplinary work on youth, with a specific focus on the body. The authors engage with conceptual, empirical and pedagogical approaches which counteract perspectives that view young people's bodies primarily as 'problems' to be managed, or as sites of risk or deviance. The authors demonstrate that a focus on the body allows us to explore a range of additional dimensions in seeking to understand the experiences of young people. The research is situated across a range of sites in Australia, North America, Britain, Canada, Asia and Africa, drawing on a range of disciplines including sociology, education and cultural studies in the process. This collection aims to demonstrate - theoretically, empirically and pedagogically - the implications that emerge from a reframed approach to understanding children and youth by focusing on the body and embodiment.
Chapter 1 Introduction - Learning Bodies: The body in youth and childhood studies -- Section 1 The young body: Gender and sexualities -- Chapter 2 Queer youthscapes in Asia: Embodied modernities and trans-embodiments -- Chapter 3 Broad minds, narrow possibilities: The embodiment of gender -- Chapter 4 Steeling the junior body: Learning sport and masculinities in the early years -- Chapter 5 "They've always got flat tummies and it really bugs us" -- Chapter 6 "Fuck your body image": Teen girls' Twitter and Instagram feminism in and around school -- Chapter 7 Internet sex chatting and "Vernacular Masculinity" among Hong Kong Youth -- Section 2 The young body: Reconceptualising health, illness and recovering -- Chapter 8 The resisting young body -- Chapter 9 Girls and sexting: The missing story of sexual subjectivity in a sexualized and digitally-mediated world -- Chapter 10 Recovering bodies: The production of the recoverable subject in eating disorder treatment regimes -- Chapter 11 G major to A minor 7 (A Progression to Recovery) -- Chapter 12 'She was becoming too healthy and it was just becoming dangerous': Body work and assemblages of health -- Section 3 Embodying research and pedagogy -- Chapter 13 'Sticky' learning: Assembling bodies, objects and affects at the museum and beyond -- Chapter 14 Moving and making bodies: Materiality as a feminist issue -- Chapter 15 Playing the inside out: Using drama as an embodied medium through which to work on changing gender norms -- Chapter 16 Visual ethics with and through the body: The participation of girls with disabilities in Vietnam in a photovoice project -- Chapter 17 Learning Bodies: Towards embodied theories, methodologies and pedagogies.
Keywords: Sociology; Early childhood education